2016
DOI: 10.1007/s11892-016-0806-7
|View full text |Cite
|
Sign up to set email alerts
|

The Expanding Role of Natural Killer Cells in Type 1 Diabetes and Immunotherapy

Abstract: Treatments for autoimmune diseases including type 1 diabetes (T1D) are aimed at resetting the immune system, especially its adaptive arm. The innate immune system is often ignored in the design of novel immune-based therapies. There is increasing evidence for multiple natural killer (NK) subpopulations, but their role is poorly understood in autoimmunity and likely is contributing to the controversial role reported for NKs. In this review, we will summarize NK subsets and their roles in tolerance, autoimmune d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 114 publications
2
25
0
Order By: Relevance
“…Most studies addressing NK cells in T1D have focused on their cytotoxic function, whereas studies investigating the phenotype of cell subsets are limited (52,53). It has been recently shown that children with newly diagnosed T1D had reduced frequencies of CD16 + CD56 dim and CD16 − CD56 dim NK cell subsets than HC (32).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies addressing NK cells in T1D have focused on their cytotoxic function, whereas studies investigating the phenotype of cell subsets are limited (52,53). It has been recently shown that children with newly diagnosed T1D had reduced frequencies of CD16 + CD56 dim and CD16 − CD56 dim NK cell subsets than HC (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact role of this latter subset in normal physiological conditions, as well as in autoimmune diseases, remains to be defined. enterovirus) [16]. 2f-h and Supporting information, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature deals mainly with two main subsets of NK cells: (1) CD56 dim CD16 + are mature cells forming the majority of NK cells in peripheral blood; and (2) CD56 bright CD16cells are considered to be immature NK cells [15]. These cells have also been termed NK eff cells and NK reg cells, respectively [16]. There is also an intermediate subset characterized as CD56 bright CD16 + [15], and some studies suggest a fourth population of NK cells, which express CD56 but lack CD16 (CD56 dim CD16 -) [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible roles for innate immune cells exist not only in the initiation stage of autoimmune diseases but also in the modulation and propagation of inflammation and tissue destruction. Such roles have been proposed for neutrophils (4), natural killer cells (5, 6), macrophages (7), dendritic cells (8, 9), innate lymphoid cells (10), and mast cells (11). Eosinophils have been recognized as a part of the inflammatory infiltrate in several organ-specific autoimmune diseases, but their potential role in autoimmune diseases has not been addressed comprehensively.…”
Section: Introductionmentioning
confidence: 99%